Effects of energy-protein supplementation frequency on performance of primiparous grazing beef cows during pre and postpartum - Moura, Felipe Henrique de (2018)
The present study was performed to evaluate the effects of energy-protein supplementation and supplementation frequency during pre (105 d before calving) and postpartum (105 d after calving) of primiparous beef cows on performance and metabolic characteristics under grazing conditions. Twenty-four pregnant Nellore primiparous cows with average BW of 409±8.0 kg, 22±0.9 mo old and 172±2.5 d of gestation were used in this trial. Treatments were randomly assigned to primiparous cows: Control (ad libitum mineral mix), Daily Supplementation (1.5 kg/d of concentrate/animal) and Infrequent Supplementation (4.5 kg of concentrate/animal every three days). The BW, ADG, BCS, fat-thickness and ribeye area (RA) were evaluated at pre and postpartum period. Two 9-d intake-digestibility trials were performed throughout the experimental period where the first at 55 d before parturition, and the second at 55 d after parturition. Concentrations of glucose, IGF-1, NEFA, - OH, cholesterol and triglycerides were used as indicators of energy status, and free amino acids (AA), serum urea nitrogen (SUN), total protein, albumin and globulins were used as indicators of proteic status collected at 27 and 9 d before parturition, at the day of parturition, 9 and 27 d after parturition. Globulins were calculated subtracting the albumin quantified from the total protein level. Biopsies of hepatic and skeletal muscle tissues were performed at 27 d prior to calving to evaluate ureagenesis and energy metabolism biomarkers. Serum progesterone (P4) level was evaluated at the 36 th d postpartum. The response variables were analyzed using PROC MIXED of SAS 9.4 (SAS Inst., Cary, NC). The frequency of supplementation did not alter (P > 0.10) BW, adjusted BW at day of parturition (adjBW), BW after calving upon parturition (calvingBW), ADG, BCS, RA and fat-thickness during pre and postpartum. The BW (P = 0.079), adjBW (P = 0.078) and ADG (P = 0.074) were higher for supplemented cows during the prepartum. The BCS (P = 0.251), RA (P = 0.352), fat-thickness on longissimus muscle (P = 0.199) and on Biceps femoris muscle (P = 0.924) were not affect by supplementation during the prepartum. At 105 d after calving the supplementation did not affect (P > 0.10) BW, ADG, BCS, RA, and fat-thickness. Birth BW of calves, ADG and calf BW 105 d after calving were not different (P > 0.10) according to supplementation and frequency of supplementation. The total dry matter intake and forage voluntary intake were not affected by supplementation and supplementation frequency during prepartum (P > 0.10) and postpartum (P > 0.10). Daily supplemented animals had higher (P < 0.001) glucose levels than animals supplemented every three days. Interaction between treatment and sampling time was significant for AA (P < 0.001), glucogenic AA (P < 0.001), ketogenic AA (P < 0.001), gluco/ketogenic AA (P < 0.001), and SUN (P = 0.005). The supplementation and frequency of supplementation did not alter (P > 0.10) the levels of IGF-1, NEFA, -OH, cholesterol and triglycerides. Likewise, the supplementation and frequency of supplementation did not alter (P > 0.10) the levels of total protein, albumin and globulins. The protein abundance of carbamoyl phosphate synthase-1 (CPS-1), mRNA levels of carnitine palmitoyltransferase-1 (CPT-1) and peroxisome proliferator-activated receptor coactivator-1α (PGC-1α) were not affected (P > 0.10) by supplementation and supplementation frequency. Similar percentage (P = 0.606) of cows with ovarian activity (P4 > 1 ng/ml) and conception rate (P = 0.842) were observed among the treatments. The energy-protein supplementation during pre and postpartum of primiparous beef cows under grazing conditions do not improve performance and metabolic characteristics. However, the reduction of frequency of supplementation do not result negative effects on performance and metabolic characteristics.